Pengaruh Gaya Kepemimpinan Transformasional, Beban Kerja, dan Kompensasi terhadap Turnover Intention Karyawan Bank BDE Yogyakarta - Sarjono Daru Prihatin; Tri Harsini Wahyuningsih (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2023)
The purpose of this study was to analyze the effect of transformastional leadership style, workload, and compensation on employee turnover intention of Bank Bhakti Daya Ekonomi (BDE) Yogyakarta. Bank BDE is one of the private BPRs in Yogyakarta that serves the micro, small and medium business sector with 178 employees. This company has received an award in the 2020 Infobank award as a BPR with the title “VERY GOOD” for its financial performance. A sample of 123 employees was determined using the slovin method which was then taken from all existing branch offices using a proportionate stratified random sampling technique. The instrument test was carried out after the data was collected, followed by a normality test as well as a classic assumption test to then test the hypothesis. Based on testing with the t test and multiple regression, it was found that the transformational leadership style has no effect on turnover intention because of the significance value of 0,685. Workload has a positive effect on employee turnover intention because the results of the t test show a significance value of 0,000 intention, as indicated by the results of the t test which has a significance value of 0,003 and a regression coefficient of -0,089. The variable ability of transformational leadership style, workload, and compensation in explaining variations in turnover intention is 40,3%, the rest is explained by other variables not examined.